Mental health, perceived social support, and sense of belonging among immigrants - Zahra Jafari; Mohammad Habibnezhad; Maryam Mirzaei Hotkani; Emily Balkam; Kolten C. MacDonell; Ellen Hickey (PLoS ONE, 2026)
Objectives Immigrants often encounter unique challenges that can adversely affect their mental health and social well-being. This research aimed to examine the mental health status (anxiety and depression), perceived social support, and sense of belonging among immigrants from non-English-speaking backgrounds in Canada, and to identify contributing factors. Methods The research included 144 Farsi- and Arabic-speaking adults, with a mean age of 36.50 years; 51.40% had resided in Canada for less than three years. All participants completed validated Farsi or Arabic versions of the Generalized Anxiety Disorder 7-item scale (GAD-7), Patient Health Questionnaire 9-item (PHQ-9), Multidimensional Scale of Perceived Social Support (MSPSS), and Challenged Sense of Belonging Scale (CSBS) in their primary language. Results Among participants, 25.70% reported symptoms of generalized anxiety (16.70% moderate, 9.00% severe), and 26.40% exhibited symptoms of major depression (20.80% moderate, 5.60% moderately severe). The overall sense of belonging was slightly above moderate, and one-third of participants reported moderate or low levels of perceived social support. Lower levels of perceived social support were significantly associated with higher anxiety and depression scores. Younger age, active job-seeking status, lower economic status, shorter length of residence in Canada, and limited English language proficiency were significant contributing factors. Conclusion Rates of anxiety and depression in this population were considerably higher than those reported in the general Canadian population and comparable studies. These findings highlight the importance of addressing mental health and social well-being among immigrant populations and can inform the development of tailored, community-based support initiatives.